2016
DOI: 10.7554/elife.14985
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioral-state modulation of inhibition is context-dependent and cell type specific in mouse visual cortex

Abstract: Cortical responses to sensory stimuli are modulated by behavioral state. In the primary visual cortex (V1), visual responses of pyramidal neurons increase during locomotion. This response gain was suggested to be mediated through inhibitory neurons, resulting in the disinhibition of pyramidal neurons. Using in vivo two-photon calcium imaging in layers 2/3 and 4 in mouse V1, we reveal that locomotion increases the activity of vasoactive intestinal peptide (VIP), somatostatin (SST) and parvalbumin (PV)-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
282
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(337 citation statements)
references
References 41 publications
40
282
5
Order By: Relevance
“…During locomotion, fluctuations in activity are reduced and both inhibitory neurons and excitatory neurons increase their firing, but inhibitory neurons are modulated more strongly in our recordings (Figure 7). There is controversy in the literature as to whether somatostatin-positive (SOM+) inhibitory neurons increase their activity during running, but several studies have found an increase in putative parvalbumin-positive (PV+) inhibitory neuron firing during running (Niell and Stryker, 2010; Polack et al, 2013; Vinck et al, 2015; Pakan et al, 2016), consistent with our results.…”
Section: Discussionsupporting
confidence: 88%
“…During locomotion, fluctuations in activity are reduced and both inhibitory neurons and excitatory neurons increase their firing, but inhibitory neurons are modulated more strongly in our recordings (Figure 7). There is controversy in the literature as to whether somatostatin-positive (SOM+) inhibitory neurons increase their activity during running, but several studies have found an increase in putative parvalbumin-positive (PV+) inhibitory neuron firing during running (Niell and Stryker, 2010; Polack et al, 2013; Vinck et al, 2015; Pakan et al, 2016), consistent with our results.…”
Section: Discussionsupporting
confidence: 88%
“…However, when combined with stimulus presentation, SOM interneurons increased their stimulus-driven firing rate during locomotion [51]. Recording activity of VIP, SOM and PV interneurons during still periods or locomotion in darkness or with visual stimulation revealed differential effects of locomotion on neuronal responses depending on the presence of visual stimulation [55]. During visual stimulation, interneurons from all three interneuron classes increased their responses with locomotion, challenging the generality of the VIP disinhibitory network as the mechanism underlying increases in stimulus driven excitatory responses during locomotion, and suggests that the action of VIPs may be both stimulus and behavioral-state dependent.…”
Section: Role Of Interneurons In Behavioral State Modulationmentioning
confidence: 99%
“…It is important to know the exact conditions of experiments in order to correctly define the roles of neural subtypes [e.g. 55] to avoid confounding effects, for example, the arousal state of the animal [62]. Furthermore, it will be important in the future to corroborate findings or compare differences with other animals, as application of optogenetic tools in other animal models improves [e.g.…”
Section: Future Goals For Investigation Of the Function Of Inhibitionmentioning
confidence: 99%
“…Previous studies have reported this preceding activity in upper layers as well as in deep layers using electrophysiological recordings in the V1 (Ayaz et al, 2013; Erisken et al, 2014; Vinck et al, 2015). Recent work has suggested that similar activity can originate from inhibitory interneurons (Polack et al, 2013; Reimer et al, 2014; Pakan et al, 2016), especially parvalbumin-positive interneurons (Polack et al, 2013; Pakan et al, 2016). In addition, this activity is probably the result of a combination of visual- and motor-related inputs (Ayaz et al, 2013; Erisken et al, 2014), which may reflect the interaction between animal locomotion and its environment.…”
Section: Discussionmentioning
confidence: 99%
“…These require the implementation of optical fibers, fiber-like GRIN lenses or miniaturized head-mounted imaging devices (Grienberger et al, 2012). Along with the current application of cell type-specific labeling of genetically encoded calcium indicators (Hires et al, 2008; Mank and Griesbeck, 2008), these approaches are strongly facilitating our understanding of the contributions of specific neuronal circuits to animal behaviors (Jung et al, 2004; Lütcke et al, 2010; Keller et al, 2012; Ayaz et al, 2013; Ziv et al, 2013; Adelsberger et al, 2014; Jennings et al, 2015; Flash and Bizzi, 2016; Pakan et al, 2016). A particularly simple but efficient method for deep tissue measurements in freely moving animals is the optical fiber-based Ca 2+ recording approach, also termed fiber photometry (Gunaydin et al, 2014; Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%